Penerapan Metode Pembelajaran Bagi Anak Diskalkulia Pada Anak Usia Dini - Ulfa Kiranti; Desi Fitri Ramadhani; Anisah Aulia; Supia Supia; Nevi Darmayanti (Universitas Maritim AMNI Semarang, 2023)
Dyscalculia is a skill disorder in exploring mathematics, whether it's exploring the concept of numbers, operating numbers, and their application. Students with dyscalculia are students who have a diagnosis of the central nervous system which can affect their learning process, especially in mathematics. As for the research method In this study the researcher used a type/research approach in the form of Library Research.